2008
DOI: 10.1002/app.28292
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and thermal properties of silyl‐terminated polycaprolactone–polysiloxane modified epoxy resin composites

Abstract: With a direct nucleophilic addition between À ÀOH groups of polydiol and À ÀNCO of a silane, a blend of silyl-terminated polycaprolactone PCL-Si and silyl-terminated polydimethylsiloxane PDMS-Si oligomer, PCS-2Si, were firstly prepared, and then blended with a commercial epoxy resin (diglycidyl ether of bisphenol-A, DGEBA) to form a ternary composite. The formed ternary composites of different content of DGEBA were cured using a polyamidoamine as a curing agent and a sol-gel process at ambient temperature. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The 29 Si NMR spectrum shown in Figure 4(a) also establishes the structure of AGPMS. The peak at 7.4 ppm attributes to O-Si(CH 3 ) 3 , the peaks at -18.9~-23.9 ppm represent the absorptions of O-Si(CH 3 ) 2 -O, and the peak at -45.2 ppm attributes to -CH 2 -Si(OCH 2 CH 3 ) 3 . And the molar ratio of GPPMS and APTES was 1/1, plus the weak reactivity of the epoxide groups of the GPPMS and the big steric hindrance of the -NH-, indicate that most AGPMS has the structure shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 29 Si NMR spectrum shown in Figure 4(a) also establishes the structure of AGPMS. The peak at 7.4 ppm attributes to O-Si(CH 3 ) 3 , the peaks at -18.9~-23.9 ppm represent the absorptions of O-Si(CH 3 ) 2 -O, and the peak at -45.2 ppm attributes to -CH 2 -Si(OCH 2 CH 3 ) 3 . And the molar ratio of GPPMS and APTES was 1/1, plus the weak reactivity of the epoxide groups of the GPPMS and the big steric hindrance of the -NH-, indicate that most AGPMS has the structure shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 However, pure poly (dimethylsiloxane) (PDMS) had very little use as a toughening agent because of the poor compatibility between soft segments of PDMS and polar hard segments in epoxy which largely resulted from the lack of hydrogen bonding. 3,4 To improve the compatibility of polysiloxane with epoxy matrix, a large number of researches have been conducted, including using silane coupling agents, 5,6 introducing polar functionality to polysiloxanes (such as capped with hydroxide, 7 amino, 8-10 epoxide, 11-13 carboxyl 14 and isocyanate group 15 ), adding block or graft silicone to make polysiloxane homogeneously dispersed in the matrix, [16][17][18][19][20] and chemical incorporation of PDMS into the main chain of epoxy. [21][22][23] Unfortunately, there still existed some drawbacks in these systems, such as the swift decline of glass transition temperature with an increase of the PDMS soft segment.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, pure poly(dimethylsiloxane) (PDMS) had very little use as a toughening agent because of the poor compatibility between soft segments of PDMS and polar hard segments in epoxy which largely resulted from the lack of hydrogen bonding. 5,6 To improve the compatibility of polysiloxane with epoxy matrix, a large number of researches have been conducted, including using silane coupling agents, 7,8 utilizing functional polysiloxanes (such as capped with amino, [9][10][11] epoxide, [12][13][14] hydroxide, 15 isocyanate group 16 and carboxyl 17 ), adding block copolymers containing silicone to make polysiloxane homogeneously dispersed in the matrix, [18][19][20][21] and making use of sol-gel method to bridge polysiloxane and epoxy monomers. 22 Unfortunately, there still exist some drawbacks in these systems, such as the swift decline of glass transition temperature and transparency with an increase of the polysiloxane soft segment, and most of them can not be used in toughening the LED-packaging epoxy resins.…”
Section: Introductionmentioning
confidence: 99%
“…To improve these properties, while at the same time retaining other properties, a second component such as the thermoplastics of PEEK, polyester and polyurethane, and the familiar reactive liquid rubber have been reported 2. Recently, the introduction of siloxanes as modifiers to epoxy resins is attracting more researchers in this field 1, 3, 4. Some unique characteristics of siloxane structures, such as low surface tension, good low temperature flexibility, nonflammability, and high resistance to thermal oxidation, could perhaps render them useful as epoxy modifiers.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous paper,4 alkoxysilane‐functionalized PDMS was tentatively introduced into epoxy resin through compatibilizing epoxy‐immiscible PDMS with epoxy‐miscible polycaprolactone (PCL) segments, which were attached to each other through a sol–gel process. It was experimentally shown that the compatibility between epoxy and PDMS increased with increasing content of alkoxysilane‐functionalized PDMS/PCL (PCS‐2Si).…”
Section: Introductionmentioning
confidence: 99%